The Effect Of Product Quality Of UMKM Bolu Menara On Buying Interest Of Faculty Of Economics Students - Br Tarigan, Sri Wulandari; Limbong, Nikasyah; Tampubolon, Novia Christiani; Manalu, Christin Lince Natalia; Marpaung, Debora Tarigas; Nadapdap, Yemima Eleonore; Syaputra, Iqbal; Rinaldi, Muammar (Outline Journal of Management and Accounting, 2025)
This study aims to examine the effect of product quality of Bolu Menara MSMEs on buying interest of students of the Faculty of Economics, State University of Medan. Product quality is seen as a major factor that determines purchasing decisions, especially among students. The study used quantitative methods with data collection through questionnaires distributed to 30 respondents. The results of the analysis show that the product quality of Bolu Menara has a significant and positive influence on students' purchase intention, with a contribution of 77.4%. Aspects of texture, taste, packaging, and price are important indicators in determining buying interest. The conclusion of this study is that improving product quality has the potential to increase the attractiveness of Bolu Menara as the top choice in the student market. These findings provide strategic insights for MSMEs to develop products that suit the preferences of young consumers.